MONEY DEMAND: A STUDY ON THE INDONESIAN INFLUENTIAL FACTORS - Nano Prawoto (Economic Journal of Emerging Markets, 2010)
The role of money demand in monetary policy is indisputable. This study analyzes the determinants of Indonesian money demand. It uses Insukindro-Error Correction Model, based on Keynesian and Monetarist theories. It finds that model based on Monetarist theory is preferable. Estimation on the chosen model suggests that money demand for real currency is influenced, in the short term, by total wealth, consumer price index, the red letter religious day, monetary crisis, and in the long term, by domestic interest rates, foreign interest rates, consumer price index, and stock price index. In addition, monetary policy using Certificate of Bank Indonesia, does not influence money demand.Keywords:     Money demand, keynesian and monetarist model, insukindro-error correction modelJEL classification numbers: E41, E49